The effect of religiosity during childhood and adolescence on drug consumption patterns in adults addicted to crack cocaine. Issue 5 (2nd August 2018) - Rezende-Pinto, Alexandre; Moreira-Almeida, Alexander; Ribeiro, Marcelo; Laranjeira, Ronaldo; Vallada, Homero
Abstract : Background: Although many studies suggest that religiosity is a protective factor against drug use, there is little information on its effect on drug consumption patterns of those who do use drugs. Aims: We aimed to examine if there is any relationship between religiosity during childhood and adolescence, and drug consumption in adult crack users. Method: We performed a cross-sectional study of adults addicted to crack cocaine. Logistic regression analysis was used to estimate the odds ratio for the association between religious history in the age groups 8–11, 12–14 and 15–17 years and outcome variables. Results: From a total of 531 respondents, religious involvement during childhood and adolescence was correlated to less frequent onset of drug consumption before 18 years (odds ratio 0.95, 95% CI 0.92–0.98) and less craving (odds ratio 0.95, 95% CI 0.91–0.99), mainly between the ages of 15 and 17 years. Conclusions: Religiosity provides some protection against drug consumption patterns in crack cocaine addicts. Declaration of interest: None.